Spatial Orientation Shrinks and Expands Psychological Distance. (July 2014) - Maglio, Sam J.; Polman, Evan
Being objectively close to or far from a place changes how people perceive the location of that place in a subjective, psychological sense. In the six studies reported here, we investigated whether people's spatial orientation (defined as moving toward or away from a place) will produce similar effects—by specifically influencing psychological closeness in each of its forms (i.e., spatial, temporal, probabilistic, and social distance). Orientation influenced subjective spatial distance at various levels of objective distance (Study 1), regardless of the direction people were facing (Study 2). In addition, when spatially oriented toward, rather than away from, a particular place, participants felt that events there had occurred more recently (Studies 3a and 3b) and that events there would be more likely to occur (Study 4). Finally, participants felt more similarity to people who were spatially oriented toward them than to people who were spatially oriented away from them (Study 5). Our investigation broadens the study of psychological distance from static spatial locations to dynamically moving points in space.